Mekanisme Koping dengan Tingkat Depresi pada Mahasiswa Tingkat Akhir - Muhammad Agung Krisdianto; Mulyanti Mulyanti (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2015)
Final year students whose individual maladaptive coping mechanisms would be very easy to get depressed. Less of knowledge about how to prevent and treat depression may result in fatal impact that is suicide. This inductive quantitative research with cross sectional design was aimed to know the relationship between mechanism koping with the level of depression in the last year student of the level of education ners study program college Alma Ata Yogyakarta. Samples were obtained by total sample technique which consisted of 47 respondents. Analysis test used Chi-Square test. The result of this research showed that there was a signiﬁcant relationship between coping mechanisms at the level of depression (p<0.05) however there was no signiﬁ cant relationship between coping mechanisms with age, gender, and place of residence (p>0.05).